PENGAJARAN ILMU KALAM DALAM PENDIDIKAN PESANTREN : PENDEKATAN TRADISIONAL DAN MODERN DI PONDOK PESANTREN MAHASISWA UNIVERSITAS ISLAM LAMONGAN - Putu Muchtar, Nicky Estu; vera, imelda (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2025)
This research aims to analyze the teaching of Ilmu Kalam in pesantren education through a comparative study of traditional and modern approaches. The traditional approach emphasizes early learning using the yellow book which is carried out face-to-face, while the modern approach is the same using the Yellow Book of learning but providing convenience for students who have not been able to take the Diniyah class And can access learning videos through social media, namely YouTube This study examines the effectiveness of both approaches in the context of pesantren education, by considering factors such as the quality of teachers, curriculum, learning environment, and student motivation. In addition, this study also highlights the importance of mastering mufrodat and the use of direct methods in improving the ability of kalam students (speaking skills) of students. The results of the research are expected to provide insight into how to optimize the teaching of Kalam Science in Islamic boarding schools to be relevant to demands of the times and able to form a critical mindset and a deep understanding of faith in students. This research method uses a descriptive qualitative research method.